2010
DOI: 10.1002/bsl.959
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward sex offenders and their relationship to personality traits and demographic characteristics

Abstract: The present study examined public attitudes toward the sentencing, treatment, management, and perceived dangerousness of sex offenders. Seventy-eight university undergraduates completed a 25-item attitude toward sex offenders survey developed for the present study, along with a five-factor measure of personality (NEO Personality Inventory - Revised), a demographic questionnaire, and the Paulhus Deception Scale, to control for social desirability. While participants most frequently endorsed the belief that sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 54 publications
6
60
1
7
Order By: Relevance
“…In relation to age, Brown et al (2008) and Olver and Barlow (2010) found that it had no significant influence on attitudes. Although Brown (1999) did report that participants aged between 30 and 49 held the least support for having a sex offender treatment centre located in their neighbourhood.…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 86%
See 2 more Smart Citations
“…In relation to age, Brown et al (2008) and Olver and Barlow (2010) found that it had no significant influence on attitudes. Although Brown (1999) did report that participants aged between 30 and 49 held the least support for having a sex offender treatment centre located in their neighbourhood.…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 86%
“…The existing literature on attitudes towards sex offenders is summarised in Table 1, with the literature strongly suggesting that public attitudes towards sex offenders are generally negative. The public also appear to endorse a range of myths about sex offenders, including the notion that there are high rates of offences perpetrated by strangers, that re-offence rates are very high, and that many sex offenders were themselves previous victims of sexual abuse (see Craun & Theriot, 2009;Fortney, Baker, & Levenson, 2009;Olver & Barlow, 2010). The public are shown to generally lack knowledge regarding base-rate recidivism and prevalent characteristics of offenders (Burchfield, 2012;Marteache, 2012), as well as about the positive effects of sex offender treatment (Brown, 1999;Fortney, et al, 2009).…”
Section: Attitudes Towards Sex Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…This conservative/liberal distinction, however, does not appear to be so clear in relation to responses to sexual offending. That is, these groups have been found to both endorse broadly similar levels of support for punitive measures directed at sexual offenders (Mears et.al, 2008;Olver & Barlow, 2010). …”
Section: Suggestionsmentioning
confidence: 96%
“…Offenders and specifically sex offenders may be regarded with fear and disgust (MacRitchie & Leibowitz, 2010;Olver & Barlow, 2010), often aggravated by the sensational media portrayal of offending, prisons and victims (Scott et al, 2006;Varma, 2006). Scott et al (2006) also mention attitudes about race as a factor that contributes to fear of youth offenders.…”
Section: Resultsmentioning
confidence: 99%